Project-Based Integrated Science Learning for Developing Students' Creative Thinking Skills: A Case Study at a Madrasah Tsanawiyah in Sukabumi City - Melda Yunita; Elin Driana; Sri Yuliawati; Ernawati Ernawati (Jurnal Penelitian Pendidikan IPA, 2025)
Project-based learning (PjBL) in integrated science is an innovative approach that combines various scientific concepts through problem-based projects to enhance students' creative thinking skills by offering meaningful, contextual, and challenging learning experiences. The purpose of this study was to explore the implementation of PjBL  in the integrated science subject for developing students' creative thinking skills at a Madrasah Tsanawiyah (MTs) in Sukabumi City. This study utilized a qualitative method with a case study approach. Data were gathered through observations, interviews, and document analysis. The study involved an eighth-grade integrated science teacher and 29 eighth-grade students. This study focused on project-based integrated science learning in developing students' creative thinking skills. The findings indicated that the teacher already acquired a sufficient understanding of creative thinking skills. The teacher also recognized that creative thinking skills are crucial in integrated science learning, particularly in helping students understand concepts more deeply, connect various scientific aspects, and apply concepts in real-life situations. The implementation of project-based integrated science learning at the MTs followed several stages: project planning, project execution, result presentation, and reflection. Through project-based learning, students were more motivated to think creatively, generate innovative ideas, and confidently express their opinions. Overall, project-based learning is regarded as an effective approach to fostering students' creative thinking abilities while also creating more immersive and meaningful learning experiences. These findings support the integration of project-based learning into national science education strategies and curriculum policies to enhance creative thinking skills among students across Indonesia